ADDRESSING POVERTY IN MALAYSIA: ANALYZING 2022 POVERTY STATISTICS, GOVERNMENT INITIATIVES, AND FUTURE CHALLENGES - Farah Adilla Ab Rahman; Maziatul Syima Rusly (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study examines poverty in Malaysia using 2022 statistical data, focusing on disparities across states, ethnic groups, and urban-rural divides. The findings reveal that states like Sabah (28.5%) and Sarawak (14.6%) have the highest rural poverty rates, while Bumiputera households face a higher incidence of absolute poverty (7.9%) compared to Chinese (1.9%) and Indian households (5.4%). The paper explores challenges such as policy implementation gaps, economic volatility, and regional inequalities. It also evaluates government initiatives like Bantuan Sara Hidup (BSH) and the Digital DESA Program, which have shown measurable success in alleviating poverty. The findings emphasize the need for targeted policies, enhanced digital infrastructure, and localized strategies to build long-term resilience and promote an inclusive Malaysia.